Measurement Equivalence/Invariance A Requirement To Conducting Cross-Groups Comparisons - Johnny Tanamal, Wahyunigsih., (Universitas Prasetiya Mulya, 2008)
The establishment of Measurement Equivalence/Invariance (ME/I) is a logical prerequisite to conducting substantive cross-groups comparisons, for example tests of group mean differences, invariance of structural parameter estimates. In agreement with this argument, this paper aims to (1) demonstrate the stages to establish ME/I test, (2) provide an example of ME/I application on customer satisfaction survey across three groups of consumer, (3) demonstrate the steps should be carried out if the measurement were not perceived equivalently by respondents. Conclusions and future research directions are presented.